Effect of thermo-mechanical activation of waste concrete powder (WCP) on the characteristics of cement mixtures. (2nd January 2023) - Vashistha, Prabhat; Oinam, Yanchen; Kim, Hyeong-Ki; Pyo, Sukhoon
Graphical abstract: Highlights: Activation of WCP phases at comparatively lower temperature of 650 °C. Thermo-mechanical activation of waste concrete powder (WCP) improved the reactivity. Up to 40% activated WCP can be effectively utilized without degradation of strength. The presence of cementitious phases in activated WCP were characterized. WCP based binder resulted in 37.6% less CO2 emission in comparison to OPC. Abstract: The objective of present study is to utilize and study the reactivity and hydration behaviour of thermo-mechanically activated waste concrete powder (WCP). For activation, the WCP was burned for 2 h at 650 °C, followed by mechanical grinding through ball milling. The reactivity of the activated WCP was improved significantly, as corroborated through the Chapelle test, hydration analysis and compressive strength analysis. Different blends were prepared with 10 to 40 % OPC replacement. Activated WCP was found to be effective in enhancing the reactivity of cement mixtures for all replacement proportions and developed comparable compressive strength in comparison to OPC. At 56 days, the application of activated WCP resulted in the developed of 75.5 % better compressive strength than the application of as received WCP. Mineralogical analysis exhibited the development of more secondary C-S-H gel with the formation of calcite at the later age. Using lifecycle analysis software, the replacement of 40 wt% of OPC with activated WCP was calculated with 37.6 %, 39.8 % and 19.7 % less CO2 emissions, less mineral resources consumption and less energy consumption, respectively.